Social participation for older people with an intellectual disability in Ireland - McCausland, Darren (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2016)
Background: Social participation is beneficial to quality of life and other outcomes. However, the available literature suggests that people with intellectual disabilities (ID) fare worse that others in various aspects of social participation. Rates of social participation are mitigated by a range of factors for people with ID including age. However, little is known about the social participation of older people with ID in Ireland, or the specific factors that shape their outcomes in this area. Furthermore, there has been little consensus or consistency in the ID field about the definition and measurement of participation, and the literature has focused predominantly on objective measures of participation, to the exclusion of subjective individual outcomes. Aim & Objectives: The main aim of the study was to examine the rates and outcomes of social participation for older people with ID in Ireland. Within this, the key study objectives were to: (i) Measure rates of social participation among this population using the WHO’s International Classification of Functioning, Disability and Health (ICF) as a valid theoretical framework for the study of participation; (ii) Identify factors associated with differences in rates of social participation for this population; and (iii) Examine associations between objective measures of social participation and subjective outcomes for individuals. Methods: Study objectives 1-3 examined cross-sectional quantitative data from wave 2 of the Intellectual Disability Supplement to The Irish Longitudinal Study on Ageing (IDS-TILDA), based on a representative sample of 701 people with ID aged 43 years and above in the Republic of Ireland. Results: Rates of social participation for older people with ID in Ireland were lower than comparable rates for the general older population across a number of areas of participation, including: social functioning; human rights and citizenship; education, training and occupation; social activities; local community interaction; and interpersonal relationships. Multiple factors are associated with differences in rates of participation amongst this population, including demographic factors (age; gender; and residence type), personal ability (level of ID; and functioning in ADLs, IADLs, communication and literacy), physical and mental health, and social support (family contact; family proximity; and having friends). The importance of these factors varies between different aspects of participation. Furthermore, all forms of social participation measured were positively associated with better subjective outcomes within the sample; and the majority of positive associations were statistically significant. Conclusions: Older people with ID in Ireland are at risk of worse quality of life and health-related outcomes than the general older population due to lower rates of social participation. The concept of social participation is broad and the adoption of a valid theoretical framework such as the ICF provides the basis for a comprehensive and more systematic and consistent study of this complex area. The complexity of social participation is emphasised by the multifactorial influences shaping rates and outcomes for this population. This requires a sophisticated approach to policy and practice in the area of social and community participation for older people with ID, which is rooted in principles of individualisation and person-centredness.
Keywords: Nursing and Midwifery, Ph.D.; Ph.D. Trinity College Dublin